1990
DOI: 10.1051/lait:199029
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and biological characterization of nine Streptococcus salivarius subsp thermophilus bacteriophages

Abstract: Summary -Nine bacteriophages of Streptococcus salivarius subsp thermophilus isolated from different fermentation accidents, with different geographic origins, were compared according to their genomic structures and growth characteristics. Their genomes are linear, double-stranded DNA, with complementary cohesive ends. They belong to one group and are c1assed into 2 closely related strains. The phages of the same strain show the same restriction pattern with BamHI, EcoRI, Hindlll and Pvu II. The bacteriophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 18 publications
2
32
1
Order By: Relevance
“…Data on growth parameters for S. thermophilus phages are scarce (Binetti, 2001;Deveau et al, 2008;Larbi et al, 1990;Tremblay & Moineau, 1999). Remarkably short latent periods (20e40 min) and very large burst sizes (ranging from 300 to 600 pfu per infection centre) were reported by Binetti (2001) for five of these phages.…”
Section: Geographical Origin Of Phages and Dairy Products Involvedmentioning
confidence: 98%
See 1 more Smart Citation
“…Data on growth parameters for S. thermophilus phages are scarce (Binetti, 2001;Deveau et al, 2008;Larbi et al, 1990;Tremblay & Moineau, 1999). Remarkably short latent periods (20e40 min) and very large burst sizes (ranging from 300 to 600 pfu per infection centre) were reported by Binetti (2001) for five of these phages.…”
Section: Geographical Origin Of Phages and Dairy Products Involvedmentioning
confidence: 98%
“…Still, as shown by DNA restriction patterns and host range, a great diversity of phages is often observed in cheese making, Quiberoni, Tremblay, Ackermann, Moineau, & Reinheimer, 2006;Quiberoni et al, 2003). In contrast, several authors from Europe and Argentina reported a more homogenous population of phages in yogurt production facilities (Benbadis, Faelen, Slos, Fazel, & Mercenier, 1990;Brüssow et al, 1994Brüssow et al, , 1998Bruttin et al, 1997;Fayard, Haeflinger, & Accolas, 1993;Larbi, Colmin, Rousselle, Decaris, & Simonet, 1990;Neve, Krusch, & Teuber, 1989;Quiberoni et al, 2003;Suárez, Quiberoni, Binetti, & Reinheimer, 2002). The diversity of phage populations in cheese making may be due to the rotation of multiple strains of S. thermophilus in starter cultures, as compared to yogurt starters, which are much less varied (Brüssow & Kutter, 2005;Quiberoni et al, 2006).…”
Section: Geographical Origin Of Phages and Dairy Products Involvedmentioning
confidence: 99%
“…In a study where EcoRV and EcoRI were used, researchers were able to group the phages into two classifications (Prevots et al 1989). In another study, only two groups were created, even though more enzymes were used (BamHI, EcoRI, HindIII and PvuII), but digestion was possible with BamHI (Larbi et al 1990). However, in the present study, BamHI enzymes did not have any recognition sequences in phage DNA (data not shown).…”
Section: S Thermophilus Phages Were Also Digested With Pvuii Andmentioning
confidence: 54%
“…The BamHI enzyme was found not to have a restriction site in these phage genomes. Similar restriction enzymes were used in different studies, and by adding other parameters, classification was performed (Prevots et al 1989;Benbadis et al 1990;Larbi et al 1990;Brussow et al 1994;Le Marrec et al 1997;Quiberoni et al 2003). In a study where EcoRV and EcoRI were used, researchers were able to group the phages into two classifications (Prevots et al 1989).…”
Section: S Thermophilus Phages Were Also Digested With Pvuii Andmentioning
confidence: 99%
See 1 more Smart Citation